Evaluating the responsiveness of higher education system in relation to social determinants of health - Rahele Samouei; Kamal Heidari; Sakineh Saghaeiannejad; Sedigheh Karami; Pejman Aghdak (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND AND AIM: To answer the society's health-care needs related to social determinants of health (SDH), higher education system must be responsive in training knowledgeable students and faculty members. Therefore, this study was carried out to determine the responsiveness of higher education system in relation to the SDH. METHODS: This is a content analysis study carried out using qualitative approach. Semi-structured interviews were used to gain access to the knowledge of experts in the fields of health care, education, and SDH. Sampling was carried out until data saturation was achieved during which 15 experts were selected using purposeful sampling method with highest possible variety. Data were categorized using qualitative content analysis approach. RESULTS: In total, 11 themes and 43 categories of codes were identified in semi-structured interviews with experts. A total of two approaches were identified for the training of responsive students including educational-research approach and cultural-social approach; five approaches were identified for the development of faculty members including cognitive development, executive development, evaluation, promotion and incentives, and revisions; two approaches were identified for provision of theoretical and practical education including education in a real and active environment and structural education; and finally, two approaches were identified for evaluation of students and faculty members in regard to their responsiveness to society's health needs and SDH including content and operational approaches. CONCLUSION: In general, the results of the current study indicate the need for the higher education system to use educational, research, and society-based approaches in real and social environments along with an incentive system and use of evaluation for responsiveness to society's health needs and SDH. These results can be useful for the health-care system and the higher education system.